Point‐of‐care ultrasound education to improve care of dialysis patients. Issue 2 (3rd January 2018) - Mullangi, Surekha; Sozio, Stephen M.; Segal, Paul; Menez, Steven; Martire, Carol; Shafi, Tariq
Abstract: Point‐of‐care ultrasound (POCUS) is rapidly emerging as a bedside diagnostic tool that can enhance physical diagnosis and facilitate clinical decision making. Although ultrasound is widely used by nephrologists for vascular access and kidney imaging, diagnostic POCUS skills in other anatomic areas are not part of routine nephrology training. In this narrative review, we will provide an overview of selected POCUS techniques, highlight potential uses of POCUS in routine nephrology practice, and describe a new curriculum implemented at Johns Hopkins University School of Medicine to teach diagnostic POCUS skills to nephrology fellows.